Evaluation of two short tandem repeat multiplex systems for post-haematopoietic stem cell transplantation chimerism analysis. - Ariffin, H.; Daud, S.S.; Mohamed, Z.; Ibrahim, K.; Lee, T.F.; Chong, L.A. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2007)
INTRODUCTION: The follow-up of chimerism status after allogeneic haematopoietic stem cell transplantation (HSCT) is essential to predict successful engraftment to assess the development of graft-versus-host disease, graft rejection and disease relapse. Analysis of short tandem repeats (STR) via polymerase chain reaction is frequently used for chimerism determination. However, most commercially-available kits have been designed for forensic purposes and may not be optimal for chimerism analysis. The present study aims to identify suitable STR markers for patient-donor pairs of predominantly Malay and Chinese ethnicity using two commercially-available forensic kits.